PENGARUH KONSENTRASI EKSTRAK KAYU MANIS (CINNAMOMUM BURMANII) TERHADAP KEKASARAN PERMUKAAN RESIN AKRILIK HEAT CURED - Viona Dian Sari; Diana Setya Ningsih; Nanda Elvira Soraya (Journal of Syiah Kuala Dentistry Society, 2016)
AbstractHeat cured acrylic resin is material that mostly used as a denture base. Cinnamon extract contains polyphenol which will make rough on the surface if it contact with acrylic resin. Aim of this research was to derermined the effect of cinnamon (Cinnamomum burmanii) extract concentration to surface roughness of heat cured acrylic resin. This research used 30 heat cured acrylic resin as specimens in size 20x20x2mm, 10 specimens for each concentrations of 40%, 50% and 60%. The specimens were immersed in aquades for 24 hours and tested the first surface roughness, and immersed in cinnamon extract with a concentration of 40%, 50% and 60% for 4 days. Each specimens tested the second roughness by using Surface Roughness Tester. Data was analyzed by paired t-test and one way ANOVA. Result showed a significant differences (p0,05) between the roughness before and after immersed in cinnamon extract concentrations of 40%, 50% and 60%. There was a significant differences (p0,05) between the concentration of 40% and 50% to the concentration of 60%, and no significant differences between the concentration of 40% and 50%. Concluded that the surface roughness of heat cured acrylic resin increases with increasing of cinnamon (Cinnamomum burmanii) extract concentration.Keyword: heat cured acrylic resin, cinnamon extract, surface roughness